Gravitational Lensed System Q2237-0305 in 2001–2008: Observations at the Maidanak Mountain - Dudinov, V. N.; Smirnov, G. V.; Vakulik, V. G.; Sergeev, A. V.; Kochetov, A. E. (Видавничий дім «Академперіодика», 2012)
Results of multicolor observations of the gravitational lens system Q2237+0305 in 2001–2008 with the 1.5-m AZT-22 telescope (Maidanak Mountain, Uzbekistan) are presented. The photometry method is described briefly. Comparison of the results of our photometry with those of the OGLE data allowed obtaining a reduction formula for these data series. Our photometry errors are estimated, demonstrating that the OGLE photometry errors are but slightly smaller than ours. The quantitative estimates of brightness variations in Q2237+0305 that arise separately from microlensing and the internal quasar variability are obtained.